Preeclampsia and Long-term Renal Function in Women Who Underwent Kidney Transplantation. Issue 1 (January 2018) - Vannevel, Valerie; Claes, Kathleen; Baud, David; Vial, Yvan; Golshayan, Delaviz; Yoon, Eugene W.; Hodges, Ryan; Le Nepveu, Anne; Kerr, Peter G.; Kennedy, Claire; Higgins, Mary; Resch, Elisabeth; et al.
Abstract : OBJECTIVE: Preeclampsia often complicates pregnancies after maternal kidney transplantation. We aimed to assess whether preeclampsia is associated with kidney function decline either during the pregnancy or in the long term. METHODS: We performed an international multicenter retrospective cohort study. Renal function at conception, pregnancy outcomes, and short- and long-term graft outcomes were collected for women who were pregnant after renal transplantation and had transplant and obstetric care at the participating centers. In women who had multiple pregnancies during the study period, only the last pregnancy was included. Univariate and multivariable analyses were performed. RESULTS: We retrieved pregnancy outcomes and long-term renal outcomes for 52 women. Chronic hypertension was present at baseline in 27%. Mean estimated glomerular filtration rate (GFR) at start of pregnancy was 52.4±17.5 mL/min/1.73 m 2 . Mean estimated GFR at delivery was 47.6±21.6 mL/min/1.73 m 2, which was significantly lower than at conception ( P =.03). Twenty women (38%) developed preeclampsia. In multivariable analysis, women who developed preeclampsia had a 10.7-mL/min/1.73 m 2 higher drop in estimated GFR between conception and delivery than women who did not develop preeclampsia ( P =.02). Long-term estimated GFR follow-up was obtained at a median of 5.8 years (range 1.3–27.5 years). Mean estimated GFR at last follow-up was 38±23 mL/kg/1.73 m 2 . Seventeen women (33%) experienced graft loss over the follow-up period. Incidence of graft loss was similar in women with and without preeclampsia in their last pregnancy (30% and 34%, respectively; P =.99). In multivariable analysis, the decrease in estimated GFR between conception and last follow-up was similar in women who experienced preeclampsia during pregnancy and those who did not (difference −2.69 mL/min/1.73 m 2, P =.65). CONCLUSION: Preeclampsia commonly complicates pregnancies after renal transplantation but is not associated with long-term renal dysfunction or graft loss. Abstract : In women who have undergone a renal transplant, preeclampsia is not associated with long-term renal dysfunction or graft loss.